PERKEMBANGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KONVERSI LAHAN SAWAH SERTA DAMPAK EKONOMINYA - ILHAM, NYAK; SYAUKAT, YUSMAN; FRIYATNO, SUPENA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
Economic growth needs more and more land for infrastructures development. It was suggested that the development would convert wet rice field to non-agriculture use. This problem suggested will threaten sustainability of national rice production. The aims of this study are: (1) to analyze growth of wetland conversion in Indonesia. (2) To identify factors that affect wet land conversion. (3) To identify economic impacts of wetland conversion, especially on rice production. The data source is from BPS as time series data from 1978 to 2000. The data and information was analyzed by descriptive and using tabulation. Some important conclusions are: (1) the wetland conversion in Java bigger than other region and tend to increase. This condition indicated that government effort to control wetland conversion was not effective yet. (2) At the macro level, wetland conversion positive associated with GDP growth, negative associated with farmer change value, no associated with increasing population. (3) The rice production losses caused wetland conversion cannot be supported by new wetland construction, so that Indonesia must import rice to suffice staple food, (4) beside improving the accuracy data and law enforcement, the construction new wetland, improvement technology on wet land and up land rice cultivation and, improvement of extension activity should be realized.
Keywords: Land Conversion, Wetland, Impacts.